THE IMPORTANCE OF VOCABULARY IN LEARNING ENGLISH LANGUAGE - Nizomova Kamola Islamovna (Journal of new century innovations, 2023)
ABSTRACT The growing need and importance of English language at the present day has made the acquisition of this language as an important requirement for today’s student. As English is perceived as an indispensable tool in order to survive in the global economy, the demands for English language have grown. Despite the importance and need of English language, it has generally been observed in the developing contexts that students having strong language competencies easily get entry into higher institutions while such entry is denied to those who have poor background in English language. The importance of English language is even more intense at secondary level as this transitional stage prepares learners to the modern life where English is everywhere. As a result, English language has been a means of either success or failure. Support for this interpretation comes from Beglar David who argues that it is the language which facilitates all other learning